Hilirisasi Mineral Pengelolaan Nikel di Indonesia: Regulasi serta Dampak Implementasinya Pada Ekonomi dan Pembangunan Smelter - Syamsul Hidayat (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Nickel is one of the important mining materials in Indonesia due to its significant resources and reserves availability. This paper discusses the downstream management of nickel mining materials by taking regulations, economic impacts and smelter development issue in one frame of discussion. Mining Law 4/2009 amended by Mining Law 3/2020 is the base regulation for downstream mining policy in Indonesia, including for nickel. Obligation of mineral processing and refining domestically and restrictions of nickel exports are two main issues that have multiple impact in nickel management process. The relative increase of annual nickel production is part of the economic impact of downstream policy. Export restrictions affect the fluctuation of nickel production volume and have an impact on economic relations between Indonesia and consumer countries, resulting in a lawsuit by European Union against Indonesian government. On the other hand, the construction of nickel smelters encourages value of nickel exports, absorption of local labor and encourage micro economic activities. It takes time to implement smelter construction in sufficient quantities as mandated in the Regulation. Projections of market absorption capacity, infrastructure such as electricity facilities, technology and capital are mine factors that influence its implementation